Thrips atactus (Thysanoptera, Thripidae): first records of the male and host plant, intercepted in quarantine at Japan - Masumoto, Masami; Minoura, Kazushige (Zootaxa, 2011)
Thrips atactus Bhatti was described from a single female taken without host data at Sibpore, West Bengal (Bhatti, 1967, 1980), and this has remained the only known specimen apart from some adults recorded by Palmer (1992) from Nepal. Thus no biological information is available about this species. In Japanese plant quarantine, this species has been intercepted several times on Eryngium foetidum [Umbelliferae] from Laos and Thailand, also on roses from Nepal. Moreover, a male adult was intercepted recently together with a female adult. The male adult is here described for the first time, and the host plant recorded. The specimens were intercepted on imported plants by plant quarantine inspectors at Narita airport and Chubu airport, Japan. Thereafter, all specimens were mounted into Canada balsam after dehydration through an ethanol series, and slide mounted for microscope study. Abbreviations as follows are used: CB=Chubu airport, CPS=campaniform sensorium, NR=Narita airport.